Orthopedic Oncology – “The Challenges Ahead” - Puri, Ajay (Frontiers in Surgery, 2014)
Orthopaedic oncology one of the relatively newer sub specialties in orthopaedics has seen rapid strides in recent years. Function preserving alternatives have largely replaced amputation as the means to achieve local control in malignant bone tumors. There is now a need to move beyond the challenge of just resection of disease and restoration of function. We must further develop various other facets as well, which include creating awareness about these lesions, rapidly propagating current information and techniques, training doctors from diverse geographical backgrounds and helping set up collaborative networks to better understand these uncommon lesions. We also need to encourage and inculcate the ability to combine clinical expertise and experience with the judicious integration of best available scientific evidence to help develop evidence based protocols. This may necessitate questioning many established beliefs and practices and having to “unlearn, and relearn”. This would be the ideal way forward to further develop and advance this field so as to promote cost effective, rational, evidence based patient care.